Peningkatan Pemahaman Siswa Mengenai Pengaruh Media Sosial terhadap Radikalisme di Kalangan Pelajar melalui Penyuluhan Hukum tentang Paham Radikalisme: Increasing Student’s Understanding Regarding the Influence of Social Media on Radicalism among Students through Legal Education Regarding the Understanding of Radicalism - Sudiarti, Elin; Setiawan, FX Ary; Pramitha, Claudia Yuni; Taun, Dwi Tiara Putri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Social media is one of the tools currently very close to people's lives. All aspects of human life cannot be separated from social media. Students are one of the users of social media. Through social media, students can access knowledge not obtained at school. Social media is also used to spread radicalism among the younger generation, especially students. Social media is used as a tool for radicalization by individuals and groups for political and social change, especially for teenagers and the younger generation. Seeing the high rate of spread of radicalism among teenagers, especially students, through social media shows the importance of knowledge and understanding for teenagers regarding the spread of radicalism through social media. There is a lack of knowledge among teenagers regarding the dangers of spreading radicalism through social media, so it is necessary to make efforts in the form of promotive external support in the form of Legal Counseling in schools, with the main target being students.